A Novel Transient Analysis of Multiterminal VSC-HVDC System Incorporating Superconducting Fault Current Limiter - Wajid Ahmed; Premila Manohar; C. H. Hussaian Basha (International Transactions on Electrical Energy Systems)
Power transmission using a voltage source converter- (VSC-) based high-voltage direct current (HVDC) system offers autonomous control of real and reactive power, constant DC voltage polarity, and bidirectional power flow. This helps to realize the multiterminal VSC-HVDC system and its integration into renewable energy sources to meet the growing power demand. However, there is a risk of higher voltages and currents during a DC line fault. The barrier to the advancements of VSC-MTDC systems is the nonavailability of commercial, higher-rated DC circuit breakers. This necessitates research on alternative methods of DC fault-clearing schemes with available technologies. In this direction, a superconducting fault current limiter (SCFCL) is an alternative option to mitigate the problems encountered in VSC-MTDC system operation. Because of this, there are not many VSC-MTDC systems available worldwide. This paper discusses different issues associated with the transient performance of the VSC-MTDC system. A representative case involving resistive SCFCL for DC line protection is presented. The simulations are carried out in the PSCAD/EMTDC platform.